Frescoes of Saint George Church in Omorfokklisia, Kastoria (1295–1317) and Its Artistic Context - Likhenko, Anastasia V. (Actual Problems of Theory and History of Art, 2020)
Frescoes of Saint George Church in Omorfokklisia, Kastoria are a well-known monument which is usually briefly described in general, but till nowadays no special research dealt with this ensemble. In its exonarthex there is an inscription that provides the names of the emperor Andronikos II Palaiologos, his wife empress Eirene and his son Michael IX and also the date 6795 (1286–1287 A.C.). However, Michael IX was crowned in 1295 and got married in 1295 only. Thus, terminus post quem of the frescoes is 1295, while terminus ante quem is 1317 (the death of the empress Eirene). After comparative analyses had been implied, we came to the conclusion that the style of its painters was to some extend under influence of the new stylistic trend, well known for the frescoes of St. Virgin Periblepta in Ohrid and the Protos in Karyes. On the other hand, it contains some features that are common for Epirote art and some ensembles in the Northern Macedonia, produced under Epirote influence.